2019
DOI: 10.2174/1574893614666181212102749
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Recent Developments of Sequence-based Protein Feature Extraction Methods

Abstract: Background: Proteins play a crucial role in life activities, such as catalyzing metabolic reactions, DNA replication, responding to stimuli, etc. Identification of protein structures and functions are critical for both basic research and applications. Because the traditional experiments for studying the structures and functions of proteins are expensive and time consuming, computational approaches are highly desired. In key for computational methods is how to efficiently extract the features from the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(51 citation statements)
references
References 62 publications
1
50
0
Order By: Relevance
“…CTDC was used to extract the characteristics of the GPCR protein feature sequences sample, including 39 properties. Previous studies showed that feature extraction is very important for constructing the computational predictors (Wei et al, 2017a , b ; Xu et al, 2018b ; Liang et al, 2019 ; Liu and Li, 2019 ; Patil and Chouhan, 2019 ; Shen et al, 2019 ; Zhang and Liu, 2019 ; Junwei et al, 2020 ; Liu et al, 2020 ; Wen et al, 2020 ). Any two of the 39 attributes were selected and plotted using Matplotlab to obtain the sample differentiation graph of GPCRs and non-GPCRs, as shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…CTDC was used to extract the characteristics of the GPCR protein feature sequences sample, including 39 properties. Previous studies showed that feature extraction is very important for constructing the computational predictors (Wei et al, 2017a , b ; Xu et al, 2018b ; Liang et al, 2019 ; Liu and Li, 2019 ; Patil and Chouhan, 2019 ; Shen et al, 2019 ; Zhang and Liu, 2019 ; Junwei et al, 2020 ; Liu et al, 2020 ; Wen et al, 2020 ). Any two of the 39 attributes were selected and plotted using Matplotlab to obtain the sample differentiation graph of GPCRs and non-GPCRs, as shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…To build an effective prediction tool, sufficient information should be incorporated into the model, especially hidden features in protein sequences [69]- [72]. In this work, eight feature groups containing 25 feature descriptors were used to formulate the protein sequences.…”
Section: B Feature Extraction Strategymentioning
confidence: 99%
“…A feature selection algorithm can help us understand the characteristics of features, and it plays a vital role in further optimizing the algorithm and improving classification accuracy [59]. The candidate feature space selected by minimal-redundancy-maximal-relevance criterion (mRMR) is more representative [60,61].…”
Section: Feature Selectionmentioning
confidence: 99%